The last glacial termination in the Coyhaique sector of central Patagonia - Vilanova, I.; Moreno, P. I.; Miranda, C. G.; Villa Martinez, Rodrigo Patricio (My University, 2019)
Southern South America is the only continental landmass that intersects the core of the Southern Westerly Winds (SWW), and thus is important for studying their role as a driver/conduit for the initiation/propagation of climate signals since the last glaciation. Their interaction with the Southern Ocean (SO) affects global climate through its influence on high-latitude upwelling and biological productivity, deep-water convection sites and, consequently, ventilation of CO2 from the deep ocean. Variations in the SWW-SO coupled system have been postulated as fundamental drivers of climate change during glacial terminations and the current interglacial. Hence, deciphering the evolution of the SWW from sensitive locations in the southern middle latitudes is essential for understanding important climatic transitions during and since the Last Glacial Termination (T1). Terrestrial records from the central Patagonian Andes (CPA) (44 degrees-49 degrees S), however, show heterogeneities in the timing, rates, and direction of climate change during T1, impeding detailed assessment of its drivers at regional, hemispheric, and global scales. Here we present new data on glacier, vegetation, and fire-regime changes in the Coyhaique sector (45 degrees 34'S) of CPA to improve our understanding on the timing and structure of the T1, including the behavior of the SWW. Our results indicate glacial recession from the youngest Last Glacial Maximum moraines just before similar to 17.9 ka and development of an ice-dammed proglacial lake during the early stages of T1. Drainage of the ice-dammed lake, triggered by renewed glacial recession, was near-synchronous with the onset of a gradual multi-millennial trend toward arboreal dominance that started at similar to 16 ka east and west of the Andes at that latitude. We detect increased influence of the SWW at similar to 45 degrees S starting at similar to 16.6 ka, relative to the first millennium of T1, that led to positive anomalies in precipitation between similar to 16-14.4 and similar to 12.8-11.5 ka, followed by negative anomalies between similar to 11.5-9 ka. The synchronous spread of arboreal vegetation east and west of the CPA divide during T1, despite the trans-Andean precipitation contrasts, suggests an upward shift in the temperature-controlled Andean tree line, underscoring the role of deglacial warming as the critical driver for afforestation at regional scale. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Deglaciation; Last Glacial Maximum